PENGARUH PELATIHAN MULTIDISIPLIN UNTUK MENINGKATKAN PENGETAHUAN TENTANG CONTINUITY OF CARE PADA LANSIA DENGAN DIABETES MELITUS DI KOTA BANDUNG - Mambang Sari, Citra Windani; Ayu, Rahadiani; Khalifatunnisa, Faiza; Haroen, Hartiah; Juniarti, Neti (Media Karya Kesehatan, 2026)
Continuity of Care (CoC) is a healthcare approach that emphasizes continuity, coordination, and integration of care across time, providers, and levels of service. Older adults with diabetes mellitus (DM) require ongoing care because they have complex health needs, a high risk of complications, and long-term support needs for disease management. In primary healthcare settings, the implementation of CoC requires a good understanding among multidisciplinary healthcare workers. However, in Indonesia, healthcare workers’ understanding of CoC for older adults with DM remains limited. This study aimed to analyze the effect of Continuity of Care training on healthcare workers’ knowledge in caring for older adults with diabetes mellitus in Bandung City. This study used a pre-experimental one-group pretest-posttest design. The study was conducted in three community health centers in Bandung City that had nursing centers and high numbers of older adults with diabetes mellitus. The sample consisted of 33 healthcare workers, including physicians, nurses, pharmacists, and nutritionists. The training was conducted over two days in September 2025 using interactive lectures, case discussions, simulations, role-play, field practice, and evaluation. Knowledge data were collected using a questionnaire developed based on the training materials and analyzed using a paired t-test. The mean knowledge score increased from 13.82 ± 0.808 before training to 14.45 ± 0.617 after training. The paired t-test showed that the increase was statistically significant (p < 0.001). Continuity of Care training improved healthcare workers’ knowledge in caring for older adults with diabetes mellitus. Structured training may serve as an initial strategy to strengthen the capacity of healthcare workers in delivering collaborative and continuous care in primary healthcare settings. Keywords: Continuity of care, diabetes mellitus, elderly, multidisciplinary team, training.